Survey data on Vietnamese propensity to attend periodic general health examinations - Vuong, Quan-Hoang (Scientific data, 2017)
As general living standards rise, so does the demand for periodic general health examinations (GHEs). Research on the subject, however, has reached opposing conclusions on the value of GHEs, although methodological limitations in previous works make these differences hard to resolve. Here, we present data from a socio-demographic survey of behaviours and tendencies concerning periodic GHE attendance in Vietnam. These data are shown to be suitable for evaluating the impact of demographic and socio-economic elements on regular health examinations. By presenting the methods used in this survey and by describing the enquiries mentioned in the dataset, this article aims to promote data-collecting methodologies that can help policy-makers and health communicators derive practical conclusions. Design Type(s) behavioral data analysis objective Measurement Type(s) Knowledge, Attitudes, Behaviors Technology Type(s) survey method Factor Type(s) biological sex • geographic location • Socioeconomic Factors Sample Characteristic(s) Homo sapiens • Viet Nam Machine-accessible metadata file describing the reported data (ISA-Tab format)